Acute neonatal airway management - The role of laryngeal mask airway - Nair, P M C; Padmarajan, Anagha (Indian Journal of Child Health, 2021)
Positive pressure ventilation with Ambu bag and face masks or T-piece resuscitation in preterm babies have proved their worth in acute neonatal airway management. However, failure rates are high and endotracheal intubation is the final life-saving procedure. However, intubation is an invasive procedure and requires good expertise, especially for handling acute emergency situations. Expertise of trainees as well as consultants is coming down rapidly due to various reasons. In these situations, supraglottic airways (laryngeal mask airway or LMA) seem to be ideal. Here, we are reviewing the application and utility of LMA in acute neonatal airway management.